Short introduction to accounting - Barker, Richard (Cambridge University Press, 2011)
An introduction to the fundamentals of accounting and how it is used that will help students apply accounting as a usable, everyday business tool. It adopts an intuitive, informal approach to describe basic principles - what they are, why they exist and how they are used - to help students see the connections between different parts of accounting and the rest of the business world. Written by an award-winning teacher and former management accountant, it encourages students to engage with the material by using questions and worked examples to test knowledge and understanding as they read. It includes a glossary of financial terms that is a useful guide to the language of business. Part of the Cambridge Short Introductions series of concise, authoritative guides to core subjects in business and management
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Accounting